Constraining Si Particles within Graphene Foam Monolith: Interfacial Modification for High‐Performance Li+ Storage and Flexible Integrated Configuration. (3rd August 2016) - Ma, Yue; Younesi, Reza; Pan, Ruijun; Liu, Chenjuan; Zhu, Jiefang; Wei, Bingqing; Edström, Kristina
Abstract : Pulverization of electrode materials and loss of electrical contact have been identified as the major causes for the performance deterioration of alloy anodes in Li‐ion batteries. This study presents the hierarchical arrangement of spatially confining silicon nanoparticles (Si NPs) within graphene foam (GF) for alleviating these issues. Through a freeze‐drying method, the highly oriented GF monolith is engineered to fully encapsulate the Si NPs, serving not only as a robust framework with the well‐accessible thoroughfares for electrolyte percolation but also a physical blocking layer to restrain Si from direct exposure to the electrolyte. In return, the pillar effect of Si NPs prevents the graphene sheets from restacking while preserving the highly efficient electron/Li + transport channels. When evaluated as a binder‐free anode, impressive cycle performance is realized in both half‐cell and full‐cell configurations. Operando X‐ray diffraction and in‐house X‐ray photoelectron spectroscopy confirm the pivotal protection of GF to sheathe the most volume‐expanded lithiated phase (Li15 Si4 ) at room temperature. Furthermore, a free‐standing composite film is developed through readjusting the pore size in GF/Si monolith and directly integrated with nanocellulose membrane (NCM) separator. Because of the good electrical conductivity and structural integrity of the GF monolith as well as the flexibility of the NCM separator, the as‐developed GF/Si‐NCM electrode showcases the potential use in the flexible electronic devices. Abstract : Si particles are spatially constrained within graphene foam monolith using a freeze‐drying method, and impressive Li + storage capabilities are shown in both the half‐cell and the full‐cell. The presence of the deep lithiated phase, c‐Li15 Si4 is confirmed by the prototype analysis of operando X‐ray diffraction (XRD) and in‐house X‐ray photoelectron spectroscopy (XPS) techniques. A flexible, metal‐free electrode based on the proposed integrated configuration is being developed.